Reanimation – praktische Umsetzung von Leitlinien und Standards in der Klinik - Kersten, Alexander (DMW - Deutsche Medizinische Wochenschrift, 2020)
Out of hospital cardiac arrest (OHCA) requiring cardio-pulmonary resuscitation (CPR) remains a mojor public health concern. OHCA affects nearly 275 000 people in Europe annualy with more than 70 000 of those in Germany alone. It represents of the major causes of death in Europe.In 40 % of patients CPR is successful and leads to a return of spontaneous circulation (ROSC). Due to the relevance of OHCA and CPR detailed guidelines with sound scientific foundation exist. However, even after successful CPR, mortality and morbidity remain high due to the severity of underlying diseases and sequelae of OHCA and CPR itself. Thus, optimization of the initial CPR treatment with reducing overall no-flow time (time from collaps with cardiac arrest to start of CPR) and optimization and streamlining of treatment algorithms and quality in hospitals receiving patients after cardiac arrest have been a strong focus to improve overall survival. Current guidelines suggest creation of Cardiac Arrest Centers as specialized hospitals who focus on high quality of post-resuscitation care with standardized processes and interdisciplinary treatment of patients after OHCA to establish fast, secure and effective treatment that is widely available in all regions.This article will address the relevant items to be considered in daily practice of resuscitation and post-resuscitation care for cardiac arrest.
Keywords: Wiederbelebung; Postreanimationsbehandlung; Reanimation; Leitlinie